The long road to diagnosis, from gastroesophageal reflux disease, through Barrett's esophagus, to visceral hypersensitivity: a case report - Wirkijowska, Małgorzata; Mędyk, Jolanta; Patarocha, Yauheniya; Rogulski, Michał; Ślusarska, Aleksandra; Błasiak, Paulina; Mikołajec, Patryk; Huk, Ruslan; Bilecka, Barbara; Wirkijowski, Jakub (Journal of Education, Health and Sport, 2025)
Background: Visceral hypersensitivity syndrome is a condition involving excessive perception of mechanical stimuli in the intestines. In patients suffering from this disorder, physiological bowel function causes pain and discomfort. Case summary: The patient presented is a 26-year-old man with severe gastrointestinal symptoms that were difficult to manage, such as heartburn, pressure in the esophageal region, a sensation of a gullet in the throat, food retention, and frequent belching. The man had been experiencing these symptoms intermittently for four years, during which time he had been treated without success. By way of exclusion, a diagnosis of visceral hypersensitivity was made, and a low dose of amitriptyline was administered. Psychological therapy was also recommended. This treatment brought significant improvement and resulted in the resolution of his complaints. Conclusions: Visceral hypersensitivity is strongly associated with psychosocial factors, which should be taken into account when treating patients with gastrointestinal disorders. Low doses of amitriptyline may be an effective treatment option.